Levetiracetam and lamotrigine effects as mono- and polytherapy on bone mineral density in epileptic patients - El-Haggar, Sahar Mohamed; Mostafa, Tarek Mohamed; Allah, Horeya Mohamed Sad; Akef, Ghada Hassan (Arquivos de Neuro-Psiquiatria, 2018)
The purpose of this study was to determine the effect of lamotrigine (LTG) and levetiracetam (LEV) as mono- and polytherapy on biochemical markers of bone turnover and bone mineral density in Egyptian adult patients with epilepsy. Methods Forty-eight patients were divided into four groups: two received monotherapy of either LTG or LEV, and the other two groups received polytherapy comprising (valproate [VPA] + LTG or VPA + LEV). Thirty matched healthy participants were included in the study. Participants completed a nutritional and physical activity questionnaire. Biochemical markers of bone and mineral metabolism and bone mineral density of the lumbar spine were measured at baseline and at six months.Results In the LEV monotherapy group, the bone formation markers showed a significant decrease in serum alkaline phosphatase and serum osteocalcin levels while the bone resorption marker showed a significant increase in urinary deoxypyridinoline levels. After six months of treatment, bone mineral density showed a significant decrease in all treated groups, while among monotherapy groups, this significant decrease was more prevalent in the LEV monotherapy group compared with the LTG monotherapy group. Furthermore, there was significant negative correlation between urinary deoxypyridinoline levels and bone mineral density in the LEV monotherapy group.Conclusion Using new generation antiepileptics, LEV monotherapies and polytherapy showed harmful effects on bone but LTG did not.
Keywords: bone density; epilepsy